Breast Cancer Disparities: A Multicenter Comparison of Tumor Diagnosis, Characteristics, and Surgical Treatment in China and the U.S. (3rd August 2015) - Sivasubramaniam, Priya G.; Zhang, Bai-Lin; Zhang, Qian; Smith, Jennifer S.; Zhang, Bin; Tang, Zhong-Hua; Chen, Guo-Ji; Xie, Xiao-Ming; Xu, Xiao-Zhou; Yang, Hong-Jian; He, Jian-Jun; Li, Hui; et al.
Abstract: Background and Objective: Incidence of and mortality rates for breast cancer continue to rise in the People's Republic of China. The purpose of this study was to analyze differences in characteristics of breast malignancies between China and the U.S. Methods: Data from 384, 262 breast cancer patients registered in the U.S. Surveillance, Epidemiology, and End Results (SEER) program from 2000 to 2010 were compared with 4, 211 Chinese breast cancer patients registered in a Chinese database from 1999 to 2008. Outcomes included age, race, histology, tumor and node staging, laterality, surgical treatment method, and reconstruction. The Pearson chi-square and Fisher's exact tests were used to compare rates. Results: Infiltrating ductal carcinoma was the most common type of malignancy in the U.S. and China. The mean number of positive lymph nodes was higher in China (2.59 vs. 1.31, p < .001). Stage at diagnosis was higher in China (stage IIA vs. I, p < .001). Mean size of tumor at diagnosis was higher in China (32.63 vs. 21.57 mm). Mean age at diagnosis was lower in China (48.28 vs. 61.29 years, p < .001). Moreover, 2.0% of U.S. women underwent radical mastectomy compared with 12.5% in China, and 0.02% in China underwent reconstructive surgery. Conclusion: Chinese women were diagnosed at younger ages with higher stage and larger tumors and underwent more aggressive surgical treatment. Prospective trials should be conducted to address screening, surgical, and tumor discrepancies between China and the U.S. Implications for Practice: Breast cancer patients in China are diagnosed at later stages than those in America, which might contribute to different clinical management and lower 5-year survival rate. This phenomenon suggests that an earlier detection and treatment program should be widely implemented in China. By comparing the characteristics of Chinese and Chinese-American patients, we found significant differences in tumor size, lymph nodes metastasis, and age at diagnosis. These consequences indicated that patients with similar genetic backgrounds may have different prognoses due to the influence of environment and social economic determinates. Abstract : Incidence rates for breast cancer continue to rise in the People's Republic of China. The purpose of this study was to analyze differences in characteristics of breast malignancies between China and the U.S. Chinese women were diagnosed at younger ages with higher stage and larger tumors and underwent more aggressive surgical treatment. Prospective trials should be conducted to address screening, surgical, and tumor discrepancies between China and the U.S.